Tantangan Keamanan Cyber pada Inovasi Kebijakan Pemerintah di masa Pandemi Covid-19 - Robby, Uchaimid Biridlo’i; Hardi Warsono, Hardi Warsono; Dwimawanti, Ida Hayu; Yuniningsih, Yuniningsih (Jurnal Keamanan Nasional, 2021)
This paper discusses the discourse on innovations in the Indonesian government’s policies in dealing with the COVID-19 pandemic, which is faced with cyber security challenges. Digitizing the public life sector is a must in the midst of the threat of the COVID-19 pandemic which requires restrictions on direct interaction between humans. Meanwhile, cybersecurity threats are a challenge to realize technology-based policy innovations in the midst of the COVID-19 pandemic. This article uses the theoretical framework of policy innovation and cyber security to explain cyber security challenges in policy innovations by the Indonesian government in the midst of the COVID-19 pandemic. This study found that the state had a fast and agile response in dealing with COVID-19 but needed new strategies and approaches, namely collaborative while prioritizing strengthening the role of regional heads. The role of regional heads has an orientation on two things, namely, first, local accountability to protect and fulfill the rights of the people and secondly, realizing local government responsiveness to be able to understand the constraints and needs faced by the community.